A case report of fatal disseminated Mycobacterium colombiense infection in a renal transplant recipient. Issue 4 (10th April 2018) - Gosal, Jasmine; Lee, B. Craig
Abstract: We report the first case of disseminated Mycobacterium colombiense infection in a solid organ transplant recipient. Co‐infection with Cryptococcus neoformans led to fatal multisystem organ failure. We review the pathogen and host factors contributing to these opportunistic infections.